Proses Penyelesaian Pembatalan Perkawinan Karena Status Wali Nikah Yang Tidak Sah (Studi Kasus di Pengadilan Agama Karanganyar) - Wahyuningrum, Prastiwi, Nuswardani, S.H., S.U, Mutimatun Ni'ami, S.H., M.Hum (2015)
This study aims to determine the consideration in determining the evidence and the verdict on the case of cancellation of marriage because of the status of guardians are not valid and the consequences that arise after the marriage was canceled. The method used method normative approach with descriptive approach. Types and sources of data consists of primary data in the form of interviews and secondary form of literature. Data were collected through library research and field studies that create a list of questions and interview, then analyzed by qualitative analysis method. The results showed the judge in determining the verdict is based on evidence and facts the trial in accordance with Article 22 of Law No. 1 of 1974 and Article 21 paragraph (1) Compilation of Islamic Law (KHI), the judge decided to cancel the marriage issued by the Office of Religious Affairs Jumapolo Karanganyar not legal force, so that the marriage null and void. While the legal consequences after the marriage was canceled by Judgments Religion Karanganyar Number: 0004/Pdt.G/011/PA.Kra, is the marriage null and void and the marriage is deemed never existed, but not retroactive to the children who are born, husband or wife in good faith, except to the joint property when a marriage annulment based on the existence in the first marriage, and three other people as long as they acquire rights in good faith before a decision on the cancellation of the law has remained.